HABS‐Silicate Controlled Synthesis of Worm‐Like Calcite via Orientated Attachment. Issue 6 (5th February 2021) - Liu, Xiangbin; Wang, Yanling; Ma, Zaiqiang; Zhou, Wanfu; Wang, Xin; Zhou, Huajian; Wang, Xiaofeng; Wang, Jun; Shi, Weiguang
Abstract: Worm‐like calcite crystals were successfully synthesized by hydrothermal method in heavy alkylbenzene sulfonate (HABS)‐ silicate hybrid aqueous system at 45 °C for 48 h. The result indicated that HABS can affect step/kink sites on the growth face of 104 calcite by alternating Ca 2+ or CO3 2− layers, resulting a slight rotation or stacking faults of the subunits, which lead to the worm shape of crystalline aggregates by elongating parallel to the c‐axis of the rhombohedral lattice. The overlapping worm structures were obtained with the synergistic effect of HABS and silicate, which presents an additives‐mediated crystallographically self‐assembly of worm‐like units and also the inheritance of orientated attachment with rhombohedral calcite habits. Abstract : Worm‐like calcite crystals are synthesized in heavy alkylbenzene sulfonate (HABS) and silicate hybrid aqueous system. HABS affects the step/kink sites on the growth face of 104 calcite, resulting a slight rotation or stacking faults of the subunits. The overlapping worm structures were obtained with the synergistic effect of HABS and silicate. This result presents an additives‐mediated crystallographically ordered self‐assembly of worm‐like units and an inheritance of oriented attachment of rhombohedral calcite habits.